Subjects of Debt: Financial Subjectification and Collaborative Risk in Malaysian Islamic Finance - Rudnyckyj, Daromir (American anthropologist, 2017)
This article argues the Malaysian state has developed Islamic finance in conjunction with two distinct strategies of subject formation. In its first phase, in the 1980s, a central objective was the financial inclusion of Malays. Islamic finance was part of an identity-building project and intended to integrate this disadvantaged indigenous majority into the national economy. By the 2000s the state had succeeded in fostering a Malay Muslim middle class through aggressive affirmative action policies. Currently, Islamic finance is being redeployed as a technique for the neoliberal entrepreneurialization of the Malay Muslim population. Empirically, this shift is evident in efforts by experts to move Islamic finance away from a reliance on what they call "debt-based" devices to ones referred to as "equity based." This entails substituting devices that reformers contend replicate the credit and lending instruments characteristic of "conventional finance" with instruments instead premised on investment, partnership, and risk sharing that they argue more faithfully adhere to the discursive tradition of Islam. مل خ م ى تحاول هذه المقالة في نصها ان تجادل ان الدولة الماليزية قامت بتطوير التمويل الاسلامي من خلا ل مختلفتين ف — مرحلة الأولى من هذا التطوير خلال ئاثنيا ت "subject formation- استراتيجتي "تكوين رعية القرن الماضي هدفت الاستراديجة المتبعة أنذالك إلى الابماج المالي للمالفيزيد؛نم حيث في ذلك الوقت كان التمويل الاسلامي جزء من ث ر و ع بنام هوية وكان يعمل على دمج الأغلبياع المحر ٠ مة من ١ الأصليين ضمن المنظوم ة ١٢١]وطيهلماليربام وبحلول اقرن الحادي والصرين نجحت اللولهفي تبني والماج الطلق الوسمإلى من ، , اكعالة. أما ض ١ affirmative action— المكان الأصليين المسلمين من خلال سياسات ' العمل الإيجابي الحالي فيتم إعادة وزيعمنظومة التمويل الاسلامي كاسلوب لتشجيع التحول الريادي النيرليبرالي بين المكن الماليزيين المسلمين ٠ وبصورة نظرية ١ فإن مثل هذا التحول يمكن تبينه من حلال الجهود اللي يقوم بها المختصون لتحريك إلى الوسائل ااالمبدية على debt-based* التمويل الإسلامى بعيدا عن ما يسمى بالوسائل المالية"المبنية على الدين يتطلب إبدال الوسائل التي يرى الهائمون على الإصلاح، أنهاتكرر مفاهيم التسلي ف equity based— المساهمةوالقرض التي تعد صفة مميزة ”للتمويل البقليدي"، بوسائل أخرى هبتيه على اسس الاسمار و سر ١كة ونقاسم آلمدآطر والتي يراها المخصون مفاهيم تطابق بصورة اكبر ثأليد التمويل المتبع^ في الإسلا Artikel ini bertujuan untuk membincangkan perihal negeri Malaysia yang telah membangunkan ke- wangan islam seiring dengan dua strategi berbeza dalam pembentukan subjek tersebut. Dalam fasa pertama yang berlangsung sekitar tahun 1980-an, objektif utama adalah kemasukan masyarakat Melayu dalam bidang kewangan. Kewangan islam adalah sebahagian daripada projek pembangunan identiti yang bertujuan untuk mengintegrasikan majoriti daripada kelompok bumiputera yang kurang bernasib baik dalam ekonomi negara. Menjelang tahun 2000-an, negeri ini telah berjaya mengangkat kelas pertengahan Muslim Melayu asli melalui dasar-dasar tindakan afirmatif yang agresif. Pada masa ini, kewangan Islam diatur semula sebagai teknik untuk pengusahawanan neo-liberal masyarakat Melayu Islam. Secara empirik, peralihan ini amat ketara dalam usaha para pakar untuk mengggerakkan kewangan Islam dari kebergantungan pada apa yang mereka namakan peranti "berasaskan hutang" kepada apa yang disebut sebagai "berasaskan ekuiti." mi melibatkan penggantian peranti yang dihadapi oleh reformis dalam meniru ciri instrumen pinjaman dan kredit "kewangan konvensional," dengan instrumen dan bukannya berasaskan pelaburan, perkongsian, dan pengongsian risiko yang mereka teguh menekankan sebagai lebih mematuhi tradisi wacana Islam. Este artículo argumenta que el estado malasio ha desarrollado las finanzas islámicas en conjunción con dos estrategias distintas de formación de sujetos. En su primera fase en los 1980s un objetivo central fue la inclusion financiera de los malayos. Las finanzas islámicas eran parte de un projecto de construcción de identidad y estaban destinadas a integrar la mayoría indigena desfavorecida en la economía nacional. Hacia los años 2000 el estado había tenido éxito en promover una clase media musulmana malaya a través de políticas agresivas de acción afirmativa. Actualmente, las finanzas islámicas están siendo reorganizadas, como una técnica para la empresarizacion neoliberal de la población musulmana malaya. Empíricamente este cambio es evidente en los esfuerzos de los expertos por alejar las finanzas islámicas de una dependencia en lo que ellos llaman intrumentos "basados en deudas" a unos referidos como "basados en acciones". Esto implica susbsitutir los mecanismos que los reformadores sostienen reproducen exactamente el crédito y los instrumentos crediticios característicos de las "finanzas convencionales", con mecanismos en cambio fundamentados en inversiones, asociaciones, y el compartir riesgos que argumentan se adhieren más fielmente a la tradición discursiva del islam.